Results of Selective Biochemical Screening for Lysosomal Acid Lipase Deficiency and Sequencing of the LIPA Gene in the Risk Group Patients - S. V. Shtykalova; A. A. Egorova; O. S. Glotov; A. V. Kiselev; I. Yu. Kogan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to study the prevalence of lysosomal acid lipase deficiency (Wolman disease and cholesteryl ester storage disease) among high-risk patients using selective biochemical screening.Material and methods. Samples from 2805 patients are collected as dried blood spots on filter paper test forms. Biochemical study of the lysosomal acid lipase (LAL) enzyme activity was carried out according to Hamilton’s protocol of, using 4-methylumbelliferyl palmitate as a substrate and LAL inhibitor Lalistat-2. Changes in fluorescence in the wells were recorded on Wallac 1420 Multilabel Counter analyzer at absorption wavelength of 355 nm and emission wavelength of 460 nm. Sequencing of the LIPA gene (NM_001127605) was carried out on an Illumina MiSeq device (Illumina, USA) from dried blood spots from patients with reduced LAL enzyme activity to define genetic variations. Results. As a result of biochemical screening for LAL deficiency among patients from high-risk groups, 20 patients with reduced values of LAL enzyme activity were found. For 17 patients, search for mutations in the LIPA gene was carried out using NGS. In 9 patients, pathogenic genetic variants were found that led to decrease in LAL activity and the manifestation of clinical symptoms. In 100 % of detected cases, genetic mutations in the LIPA gene included single nucleotide substitution c.894G>A. Along with this mutation, two previously undescribed mutations (c.35dup and c.176A>G) were discovered in a compound heterozygous state.Conclusions. The variety of clinical symptoms and wide range of ages at which symptoms may begin (in the case of cholesteryl ester storage disease) can lead to errors in diagnosis. The c.894G>A variant is the most common variant worldwide among patients with a confirmed diagnosis of LAL deficiency and was present in all confirmed cases in this study, suggesting that this variant is the predominant mutation in the LIPA gene in Russian population. Pathogenicity status of previously undescribed discovered mutations (c.35dup and c.176A>G) needs to be determined.